Frontiers in offshore geotechnics ISFOG 2005 [compact disc] : Proceedings of the First International Symposium on Frontiers in Offshore Geotechnics, University of Western Australia, Perth, 19-21 September 2005 - International Symposium on Frontiers in Offshore Geotechnics (1st : 2005 : Perth); Gourvenec, Susan; Cassidy, Mark (Leiden : Taylor & Francis, 2005)
07